2016
DOI: 10.1002/bjs.10102
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes and their predictors at 2- and 3-year follow-up after immediate latissimus dorsi breast reconstruction and adjuvant treatment

Abstract: Clinically important changes occurred in physical functioning, breast symptoms, body image and psychological distress. These results will guide selections of key PRO domains and sample-size calculation of future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Lastly, four studies out of 11 (36%) suggested that complications had a significant impact on physical, emotional, and sexual well‐being . Menez et al reported that major complications (vs minor) were associated with lower psychosocial, emotional, and sexual well‐being, while Winters et al found that early complications (vs later) were associated with lower overall quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, four studies out of 11 (36%) suggested that complications had a significant impact on physical, emotional, and sexual well‐being . Menez et al reported that major complications (vs minor) were associated with lower psychosocial, emotional, and sexual well‐being, while Winters et al found that early complications (vs later) were associated with lower overall quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies out of six (67%) reported that chemotherapy was associated with low levels of psychosocial, sexual, and social function, and an overall lower quality of life . One study found that patients who underwent immunotherapy presented higher odds of having lower psychosocial and sexual well‐being …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…their health status had deteriorated) from baseline to 3 months however improved by 12 months post-operatively Winters et al (2016). They assessed health-related quality of life (HRQL) using validated self-report questionnaires, some of which focused on the functional impact of breast cancer and its treatment.…”
mentioning
confidence: 99%